New Sources of Biological Data Supporting Environmental History of a Tropical Forest of South-Eastern Brazil - Sales, Gabriel Paes da Silva; Guedes-Bruni, Rejan R. (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2023)
The Tijuca Forest results from a reforestation project executed in the second half of the nineteenth century, with native and exotic species planted in the mountains of Rio de Janeiro, Brazil. Aiming at a theoretical reflection, the use of integrated methodologies from different areas of knowledge was evaluated to expand the research of the environmental history of a tropical forest in south-eastern Brazil, using everything from the search for historical documents to the counting of tree growth rings. It was possible to find some of the trees from the initial reforestation efforts, to circumscribe the locations of the first plantations, hitherto unknown, as well as the original intentions of tree selection: a reflection of the silvicultural model of the period that incorporated the tropical identity of the forest without giving up the market demand. The project area indicates that the planted forest would cover approximately 330 ha, prioritizing restoration by micro basins. In the 33 years analysed, about 155,000 trees were planted (110,000 with success) from a repertoire of at least 107 species, prioritizing the native ones. The quality of the wood, mainly for the naval segment, was prioritized, but other purposes were also met. The model and selection criteria for planting areas and species characterize a strategic plan that foresaw the recovery of water sources simultaneously with the generation of wealth in the medium and long term, diversifying the use of the soil and inaugurating a cycle of silvicultural exploitation in the country. This study re-signifies the understanding of the Tijuca Forest ecology, not only in space but mainly in time, revealing the subtle relationships between tropical nature and society in formation.